Association of Genetic Polymorphisms of TGF-β1, HMOX1, and APOL1 with CKD in Nigerian patients with and without HIV. (2020)
Rationale & Objective: Recent studies in the human immunodeficiency virus (HIV)-infected population have suggested that there are genetic predispositions to the development of chronic kidney disease (CKD) in this context. We investigated the association of genetic polymorphisms of the genes encoding apolipoprotein L1 (APOL1), transforming growth factor β1 (TGFβ1; a profibrotic cytokine), and heme oxygenase 1 (HMOX1) with prevalent CKD among adults with and without HIV infection. Study Design: Case-control study. Setting & Participants: West African adults including 217 HIV-infected patients with CKD (HIV+ /CKD+ group), 595 HIV-infected patients without CKD (HIV+ /CKD− group), 269 with CKD and no HIV infection (HIV− /CKD+ group), and 114 with neither CKD nor HIV (HIV− /CKD− group). Exposure: The genetic polymorphisms with reference single-nucleotide polymorphism (rs) identification numbers rs1800469 (TGF-β1), rs1800470 (TGF-β1), rs121918282 (TGF-β1); rs60910145 (APOL1 G1 risk allele), rs73885319 (APOL1 G1 risk allele), rs71785313 (APOL1 G2 risk allele), and rs743811 (HMOX1); HIV. Outcome: CKD. Analytical Approach: Single-nucleotide poly morphism (SNP) genotyping of rs1800469 (TGF-β1), rs1800470 (TGF-β1), rs121918282 (TGF-β1); rs60910145 (APOL1), rs73885319 (APOL1), rs71785313 (APOL1), and rs743811 (HMOX1) was performed. Hardy-Weinberg equilibrium was evaluated for all SNPs, and minor allele frequencies were reported. A case control analysis was performed, and multivariable logistic regression was used to control for potential confounders. Results: Minor allele frequencies for TGF-β1 (rs1800469, rs1800470, and rs1800471), APOL1 (rs60910145, rs73885319, and rs71785313), and HMOX1 (rs743811) were 0.25, 0.46, 0.46, 0.44, 0.45, 0.17, and 0.14, respectively. Among HIV-positive individuals, only TGF-β1 rs1800470 (GG vs AA), APOL1 (in the recessive model), and hypertension were associated with prevalent CKD (adjusted ORs of 0.44 [95% CI, 0.20-0.97], 2.54 [95% CI, 1.44-4.51], and 2.17 [95% CI, 1.35-3.48], respectively). No SNP polymorphisms were associated with prevalent CKD among HIV negative individuals. Limitations: The lack of histopathology data for proper categorization of the type of HIV-related nephropathy. Conclusions: APOL1 polymorphisms were highly prevalent in this population and among adult patients infected with HIV and were associated with increased CKD risk. The TGF-β1 (rs1800470) polymorphism was associated with reduced risk, and HMOX1 polymorphisms were unassociated with CKD